Normalisasi Situs Bersejarah Benteng Jepang untuk Pengembangan Wisata Edukasi - Al Azizi, Andrewku Gharis; Iklimah, Siti Nur; Kamila, Putri; Rahmadi, Ihza Fajri; Aini, Septina Nur; Distira, Rachel Ayu (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The community service program by the Collaborative KKN 03 students aims to develop Cakru Village as a history-based educational tourism destination. The main focus of this activity is the normalization of the Japanese defense fort from the World War II era located in the village. The objectives of the activity include preserving historical sites, empowering tourism awareness groups, and increasing tourist attractions. The method used is the Participatory Action Research (PAR) approach, where students work together with the community to plan and implement the normalization and modernization of the site. The implementation of activities includes cleaning, rearranging, and utilizing technology to promote the site as an educational tourism destination. The results of this activity show an increase in public awareness of the importance of preserving history, as well as an increase in tourist visits. This activity contributes to the empowerment of the local economy and the development of the village as an attractive educational tourism.